Healthy Brain, Happy Life: A Personal Program to to Activate Your Brain and Do Everything Better - Wendy Suzuki; Billie Fitzpatrick (New York Dey St., 2015)
A neuroscientist transforms the way we think about our brain, our health, and our personal happiness in this clear, informative, and inspiring guide-a blend of personal memoir, science narrative, and immediately useful takeaways that bring the human brain into focus as never before, revealing the powerful connection between exercise, learning, memory, and cognitive abilities. Nearing forty, Dr. Wendy Suzuki was at the pinnacle of her career. An award-winning university professor and world-renowned neuroscientist, she had tenure, her own successful research lab, prestigious awards, and international renown. That's when to celebrate her birthday, she booked an adventure trip that forced her to wake up to a startling reality: despite her professional success, she was overweight, lonely, and tired and knew that her life had to change. Wendy started simply-by going to an exercise class. Eventually, she noticed an improvement in her memory, her energy levels, and her ability to work quickly and move from task to task easily. Not only did Wendy begin to get fit, but she also became sharper, had more energy, and her memory improved. Being a neuroscientist, she wanted to know why. What she learned transformed her body and her life. Now, it can transform yours. Wendy discovered that there is a biological connection between exercise, mindfulness, and action. With exercise, your body feels more alive and your brain actually performs better. Yes-you can make yourself smarter. In this fascinating book, Suzuki makes neuroscience easy to understand, interweaving her personal story with groundbreaking research, and offering practical, short exercises-4 minute Brain Hacks-to engage your mind and improve your memory, your ability to learn new skills, and function more efficiently. Taking us on an amazing journey inside the brain as never before, Suzuki helps us unlock the keys to neuroplasticity that can change our brains, or bodies, and, ultimately, our lives.
Keywords: Nonfiction; Health; Science; Neuroscience; Psychology; Brain; Memoir; Mental health